2011
DOI: 10.1029/2010tc002836
|View full text |Cite
|
Sign up to set email alerts
|

Lateral termination of the north‐directed Alpine orogeny and onset of westward escape in the Western Alpine arc: Structural and sedimentary evidence from the external zone

Abstract: [1] The initial propagation of the Western Alpine orogen was directed northwestward, as shown by basement-involved and Mesozoic sedimentary cover compressional structures and by the early foreland basins evolution. The crystalline basement of the Dauphiné zone recorded three shortening episodes: pre-Priabonian deformation D1 (coeval with the Pyrenean-Provence orogeny), and Alpine shortening events D2 (N-NW directed) and D3 (W-directed). The early Oligocene D2 structures are trending sub-perpendicular to the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 228 publications
(209 reference statements)
1
79
1
1
Order By: Relevance
“…Ma Alpine strike-slip shear zones in the basement (probably reactivating former Pyrenean faults, Simon-Labric et al, 2009;Dumont et al, 2011). In the sediments, a regional cleavage formed before 26 Ma at temperatures around 300°C (Crouzet et al, 2001), which is confirmed by the presence of pyrophyllite and cookeite in the Liassic sediments (280 to 350°C from west to east (Jullien and Goffé, 1993).…”
Section: Obtained Ages Of About 31-34mentioning
confidence: 74%
See 1 more Smart Citation
“…Ma Alpine strike-slip shear zones in the basement (probably reactivating former Pyrenean faults, Simon-Labric et al, 2009;Dumont et al, 2011). In the sediments, a regional cleavage formed before 26 Ma at temperatures around 300°C (Crouzet et al, 2001), which is confirmed by the presence of pyrophyllite and cookeite in the Liassic sediments (280 to 350°C from west to east (Jullien and Goffé, 1993).…”
Section: Obtained Ages Of About 31-34mentioning
confidence: 74%
“…1.; Ford et al, 1996 and references therein) supposedly mark the first Alpine deformation in the Western Alps, but the significance of these folds has been recently challenged by Michard et al (2010) who reinterpreted them as huge gravity structures unrelated to any compressional event. Thus, Alpine deformation probably started with pre-Priabonian E-W thrusts caused by a N-S compression mainly described in the southern Oisans massif (Gidon, 1979;Ford, 1996;Sue et al, 1997;Dumont et al, 2008Dumont et al, , 2011). …”
Section: Geological Setting and Previous Workmentioning
confidence: 99%
“…Consequently, the presence of a major kinematic "transfer zone" (Ligurian sinistral transfer, LST in Fig. 19) at the southern termination of the Western Alps arc could be envisaged as a major crustal feature that may have provided the left-lateral "southern disengaging lineament" (Giglia et al 1996) necessary for the Oligocene westward indentation (Dumont et al 2011(Dumont et al , 2012 and counterclockwise rotation (Collombet et al 2002;Rolland et al 2012) of Adria promontory, as invoked in literature during the last decades (see "Structural setting at the southern termination of the Western Alps" section for details), and roughly described as "Stura couloir" or Stura Fault.…”
Section: The "Common" Alpine Foreland Basin Successionmentioning
confidence: 99%
“…A refined view on the situation sketched by Tommasini et al (2011) would include a plate tectonic boundary between the Western Alps and the central Alps in order to explain the difference in chemical evolution for these two areas. Such a plate tectonic strike slip boundary has been proposed by several authors (e.g., Ricou and Siddans 1986;Handy et al 2010;Dumont et al 2011). This boundary explains the different evolution between the western-and the central-Alps.…”
Section: Geodynamic Evolutionmentioning
confidence: 99%